Nursing Education Amid a Pandemic: Mental Health in a Time of Virtual Learning. Issue 4 (July 2021) - Amerson, Roxanne; Fisher, Beth; Bible, Joe; Burgess, Lena; Ravan, Leslie; Ward, Linda
Abstract : Background: The unprecedented pandemic presented new stresses and challenges in nursing education impacting the mental health of nursing students. Purpose: The purpose of this study was to evaluate the relationship between virtual learning and the mental health of nursing students. Method: This study used a descriptive, cross-sectional design with a convenience sample of 256 nursing students enrolled in a baccalaureate program. Data were collected through an online survey using 2 screening tools for stress, anxiety, and depression. Results: Mean sum Patient Health Questionnaire-4 scores and subscale scores suggest that more than 40% of students experienced mild to moderate levels of psychological distress. Mean sum Perceived Stress Scale-10 scores indicate 84% of students experienced moderate levels of stress, and 14% experienced high levels of stress. Conclusions: During periods of societal crisis, faculty must be hypervigilant to the mental health needs of students. Abstract : Supplemental digital content is available in the text.